2019
DOI: 10.1021/acs.chemrev.9b00348
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of Flexible Two-Dimensional MXenes with Multiple Functionalities

Abstract: In the past decade, two-dimensional (2D) transition metal carbides, nitrides, and carbonitrides (MXenes) have attracted attention and interest from the scientific community due to their superior mechanical strength and flexibility, physical/chemical properties, and multiple exciting functionalities. Among these materials, the ingenious and effective combination of the mechanical and functional properties of MXenes provides a promising opportunity for designing flexible and wearable devices. This review summari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
213
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 301 publications
(215 citation statements)
references
References 460 publications
(981 reference statements)
2
213
0
Order By: Relevance
“…The final chemical formula of MXenes can be denoted as M n+1 X n T x ; the meaning of each letter is the same as that of MAX phases (M n+1 AX n ), except for T x representing terminated -OH, -F, and -O functional groups at surface [8,9]. Although MXenes show promising application prospect in energy storage [10][11][12], the practical electrochemical performance of MXenes falls short of expectations [13]. This poor result is probably due to the blocking effect of surface anion and excessive accumulation of layers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The final chemical formula of MXenes can be denoted as M n+1 X n T x ; the meaning of each letter is the same as that of MAX phases (M n+1 AX n ), except for T x representing terminated -OH, -F, and -O functional groups at surface [8,9]. Although MXenes show promising application prospect in energy storage [10][11][12], the practical electrochemical performance of MXenes falls short of expectations [13]. This poor result is probably due to the blocking effect of surface anion and excessive accumulation of layers [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous published reviews in the fields of MXenes for energy, catalysis, and environmental remediation [ 12 , 17 , 18 , 19 , 20 , 21 , 22 , 23 ]. However, the reviews on the mechanical properties of self-standing MXenes are not yet reported [ 24 ]. Many studies have shown that MXenes exhibits excellent mechanical ion adsorption properties, which in turn will set the stage for exploring the possibility of their use in sensors and flexible devices [ 6 , 24 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Compared to other nanomaterials, MXenes possess the following attractive properties that suitable for cancer therapy. (i) In the presence of functional groups, such as -OH, -O, or -F, MXenes are hydrophilic in nature [9,11], indicating substantial potential for surface modification.…”
Section: Applications Of Mxenes In Cancer Therapymentioning
confidence: 99%
“…Because of their unique graphene-like structure, they were named MXenes. In terms of the precursors, more than 90 MAX-phase and non-MAXphase precursors have been reported to fabricate MXenes [9,10]. MAX phase is a family of layered ternary carbides, nitrides, and carbonitrides consisting of "M", "A", and "X" layers.…”
Section: Introductionmentioning
confidence: 99%